2009
DOI: 10.1002/art.24635
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the synovial T cell repertoire in anti–citrullinated protein antibody–positive rheumatoid arthritis

Abstract: Objective. The association of HLA-DRB1 alleles with anti-citrullinated protein antibodies (ACPAs) in rheumatoid arthritis (RA) suggests the potential involvement of T lymphocytes in ACPA-seropositive disease. The purpose of this study was to investigate this hypothesis by systematic histologic and molecular analyses of synovial T cells in ACPA؉ versus ACPA-RA patients.Methods. Synovial biopsy samples were obtained from 158 RA patients. Inflammation was determined histologically and immunohistochemically. RNA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 60 publications
3
50
2
Order By: Relevance
“…This is the first study, to our knowledge, of these antibodies in lung disease, and our findings will require further validation; nevertheless, it is interesting to consider their significance. The pathogenic role of ACPA in rheumatoid arthritis is thought to involve complement activation [24] and alteration of the T-cell repertoire in the joint [25], with reaction to self as a result. Our data would suggest that this may be organ specific, occurring just in the joint despite the fact that any protein containing citrulline could be a target for ACPA.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study, to our knowledge, of these antibodies in lung disease, and our findings will require further validation; nevertheless, it is interesting to consider their significance. The pathogenic role of ACPA in rheumatoid arthritis is thought to involve complement activation [24] and alteration of the T-cell repertoire in the joint [25], with reaction to self as a result. Our data would suggest that this may be organ specific, occurring just in the joint despite the fact that any protein containing citrulline could be a target for ACPA.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on the synovial immunopathologic processes of Behçet's disease, we observed a marked synovial infiltration with mast cells in patients with psoriatic arthritis (PsA), one of the prevalent phenotypic subtypes of SpA (19). Considering the potential role of aberrant innate immune responses in the pathogenesis of SpA (9,10), this observation urged us to investigate the presence and potential role of mast cells in SpA synovitis.…”
mentioning
confidence: 99%
“…The cellular and molecular pathways responsible for the differences and commonalities between these two types of arthritis remain largely unknown. Based on a series of systematic synovial studies, we recently proposed that joint inflammation in SpA may be driven mainly by cells of the innate immune system, including specific macrophage subsets and granulocytes, whereas molecular pathways related to (auto)antigen-specific T and B lymphocyte activation predominate in RA synovitis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Besides its localization and antibody reactivity, researchers who wanted to determine the trigger for ACPA production also focused on the capacity of citrullinated proteins to induce T-cell proliferation, since there is a strong association between ACPA titers and HLA-DRB1 alleles in RA and since ACPA are class-switched antibodies [ 62 ]. The proliferative response of peripheral blood mononuclear cells to both fi laggrin and citrullinated fi laggrin was rarely observed and did not signifi cantly differ between RA patients and healthy controls [ 63 ], again indicating that (citrullinated) (pro)fi laggrin is not the trigger for RA.…”
Section: Is (Pro)filaggrin the Trigger For Acpa Production?mentioning
confidence: 99%